2016
DOI: 10.1051/matecconf/20166704005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminescent Properties in Tm3+/Dy3+Co-doped Transparent Phosphate Glass Ceramic

Abstract: Abstract.Novel Tm 3+ /Dy 3+ co-doped phosphate glass and glass ceramic samples for white light emitting diodes were prepared by melt quenching method. Under 353 nm excitation, the colors of the luminescence of the glass and glass ceramic samples are white. The CIE chromaticity coordinates (0.338, 0.328) of the emission from the glass ceramic is close to the standard white-light illumination (0.333, 0.333). Compared to the glass, the fluorescence intensity in the glass ceramic is greatly enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…[1] In particular, rare-earth doped GCs have been studied extensively for potential application in white light emitting diodes (WLEDs). [2][3][4][5][6][7][8] Properties of luminescence centres are inseparably connected with their local structure, therefore, it needs to be studied and understood thoroughly to tailor an efficient phosphor for desired applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In particular, rare-earth doped GCs have been studied extensively for potential application in white light emitting diodes (WLEDs). [2][3][4][5][6][7][8] Properties of luminescence centres are inseparably connected with their local structure, therefore, it needs to be studied and understood thoroughly to tailor an efficient phosphor for desired applications.…”
Section: Introductionmentioning
confidence: 99%
“…As S = 1/2, the ZFS term is absent in Cu 2 + EPR spectra [34,36]. For the case of axial symmetry and absence of ZFS, it is common to rewrite SH (2) in the following form: (5) In glasses, it has been observed that the g tensor component values g ‖ > g ┴ > 2 indicating that Cu 2 + ions occupy sixfold coordinated sites of distorted octahedral symmetry [37,[51][52][53]. Changes in Cu 2 + SH parameter values, depending on the composition, allow the study of crystal field variations as well as the nature of bonds with the surrounding ligands.…”
Section: Cu 2 +mentioning
confidence: 99%
“…12 and 13); however, there is little information about iron-doped glass ceramics. Fe 3 + electron configuration 3d 5 is the same as for Mn 2 + , yet EPR spectra are distinctly different due the lack of well-defined HF structure. Thus, Fe 3 + EPR spectra features in glasses can be explained by variations of second order ZFS parameters [34].…”
Section: Other Paramagnetic Centersmentioning
confidence: 99%
See 1 more Smart Citation